Integrating Hebbian and homeostatic plasticity: the current state of the field and future research directions - Keck, Tara; Toyoizumi, Taro; Chen, Lu; Doiron, Brent; Feldman, Daniel E.; Fox, Kevin; Gerstner, Wulfram; Haydon, Philip G.; Hübener, Mark; Lee, Hey-Kyoung; Lisman, John E; Rose, Tobias; et al. (Royal Society, The, 2017)
We summarize here the results presented and subsequent discussion from the meeting on Integrating Hebbian and Homeostatic Plasticity at the Royal Society in April 2016. We first outline the major themes and results presented at the meeting. We next provide a synopsis of the outstanding questions that emerged from the discussion at the end of the meeting and finally suggest potential directions of research that we believe are most promising to develop an understanding of how these two forms of plasticity interact to facilitate functional changes in the brain.This article is part of the themed issue 'Integrating Hebbian and homeostatic plasticity'.